Prevalence of Shoulder Pain in Smokers - Naseeba Naseer Ahmed, Arfa Zuha, Faiza Shareef, Affifa Sher Muhammad, Arshemah Nawaz, Numaira Anwar, Adnan Hashim (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to determine the prevalence of shoulder pain among the general population of smokers. Study design: This is an Observational cross-sectional study. Place & duration: Data was collected from the general population of smokers in Kuwait and Pakistan. This study was completed within 2 months. Methodology: This observational cross-sectional study was conducted on 115 smokers that included a proper standardized research questionnaire (internet survey), a comprehensive literature search, study inclusion criteria, screening techniques and exclusion reasons, data collection, data analysis and synthesis using IBM SPSS software. Further data collection is carried out in Pakistan and Kuwait from the general population of smokers. Results: Within the sample size of 115 smokers, 41.74% do not experience shoulder pain and 58.26% smokers have shoulder pain. Conclusion: This study concluded that there is a prevalence of shoulder pain was in smokers despite of any other musculoskeletal disorder. Smoking has an adverse reaction on bones, muscles (rotator cuff), tendons and ligaments and mainly effect the shoulder region. Keywords: Smoking, shoulder pain, musculoskeletal system